تطوير نماذج التنبؤ بالسرعة العملية على الطرق المركزية ذات الحارتين باتجاهين للحركة (Latakia University Journal -Engineering Sciences Series, 2019)
إن اختلاف سرعة القيادة بين العناصر المتعاقبة للطريق يعتبر من أهم المسببات الأساسية للحوادث المرورية, لذا يهدف البحث إلى إيجاد المعادلات التنبؤية بالسرعة العملية  V85للعربات، في مناطق المنعطفات الأفقية والاستقامات وذلك على الطرق المركزية ذات الحارتين باتجاهين. أجريت القياسات الحقلية للسرعة لأكثر من 7500 مركبة على (47) منعطفاً أفقياً و (24) استقامة واقعة على طريقي الساحل-الغاب واللاذقية-بانياس. تم إيجاد معادلات الانحدار التي تعطي قيمة السرعة العملية بالعلاقة مع نصف قطر المنعطف الأفقي R من خلال دراسة قيم معامل التحديد R2 للمعادلات التي تربط بين (R&V85), (  &V85), (  &V85) إذ أعطت العلاقة بين (  &V85) أعلى قيمة لمعامل التحديد (0.84=R2), وبناء على ذلك تم اعتماد المعادلة التنبؤية التالية: تم تطبيق اختبار (Chi-square test) إذ أكد دقة المعادلة المستنتجة. تم دراسة تباين السرعة العملية V85 بين العناصر الهندسية المتتالية (استقامة-منعطف أو منعطفين متتالين) على الطريقين المدروسين وتقييمهما وفق معايير السلامة المرورية. The variation of the vehicle driving speed between successive alignment elements is one of the main causes of accidents. The objective of this study is to develop speed prediction equations on two-lane highways for central roads. The speed of more than 7500 vehicles was measured during this study and collected at (47) curves and (24) straights on two central roads (Sahel-Ghab and Lattakia- Banias). In this search, we have concluded the regression equations that give the correlation between the operating speed (V85) and curve radius ( ), by studying the determination factor values, we have found the variable ( ) has the largest value (R2=0.84) and the considered equation is:   A Chi-square test was performed to assess the goodness-of-fit of the equation developed to predict 85th percentile curve speed. The variance of speeds between the successive geometric elements was performed to evaluate the road according to safety criterion.